Degradable organic-inorganic composite film and preparation method and application thereof

By combining calcium phosphate nanoclusters with natural polymer materials, a composite film of rod-shaped hydroxyapatite nanocrystals is formed, which solves the problem that existing degradable materials are difficult to degrade in the natural environment, and achieves the effect of natural direct degradation in the soil, and has high toughness and environmentally friendly degradation products.

CN119613781AActive Publication Date: 2025-03-14ZHEJIANG UNIV

Patent Information

Application Number
CN202411682489.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Existing degradable materials are difficult to simplify degradation conditions in the natural environment, and require industrial compost or high temperature and high humidity conditions, which increases the cost of use and recycling. At the same time, the toughness of natural polymer materials is insufficient, making it difficult to achieve effective degradation in a natural soil environment.

Method used

By preparing calcium phosphate nanoclusters combined with natural polymer materials such as carboxymethyl chitosan and alginate, rod-shaped hydroxyapatite nanocrystals with small size and high aspect ratios are formed, uniformly dispersed in the organic matrix, improving the organic-inorganic phase interface and degrading naturally directly in the soil.

Benefits of technology

It realizes natural direct degradation in the soil, with high toughness that regulates mechanical properties, and the degradation products have minor damage to the soil, and contribute to plant growth. It is suitable for packaging, agriculture and medical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613781A_ABST
    Figure CN119613781A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable organic-inorganic composite film and a preparation method and application thereof, and belongs to the technical field of composites.The method comprises the steps that 1, an organic amine stabilizer, a calcium source, a phosphorus source and an organic solvent are used for preparing a calcium phosphate nano-cluster precursor, and calcium phosphate nano-clusters are obtained through further separation; (2) mixing the calcium phosphate nano-cluster and a natural polymer material to prepare a uniformly dispersed emulsion, the natural polymer material including carboxymethyl chitosan and alginate, using the emulsion to prepare a membrane, and during the membrane preparation process, generating an evaporation-induced self-assembly process to prepare the membrane. The degradable organic-inorganic composite film is obtained by combining a rod-like hydroxyapatite nanocrystal which is formed by phase change of the calcium phosphate nanocluster and crystallization with a natural high polymer material. The organic-inorganic composite film has adjustable mechanical properties, can be naturally and directly degraded in soil, and has wide application prospects in the fields of packaging, agriculture, medical treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a degradable organic-inorganic composite film and a preparation method and application thereof. Background Art

[0002] Degradable materials are materials that meet usage requirements within their service life, and after use, they can easily disintegrate their own structure and decompose into small molecules through certain physical, chemical or biological effects. They can avoid long-term pollution to the environment and have good environmental safety. Nowadays, the expansion of human production activities has led to further aggravation of resource consumption and ecological environmental problems. The society has gradually increased its attention to the efficient use of resources and environmental protection. Degradable materials have achieved rapid development due to their low dependence on petroleum resources and low environmental pollution. Degradable materials are widely used in packaging, agriculture, medical care and other fields. They can effectively reduce the negative impact on the environment and resources, promote sustainable development, and realize specific functions such as material embedding and delivery.

[0003] Degradable materials can be roughly divided into biodegradable materials, photodegradable materials and chemically degradable materials according to the specific degradation pathways. Among them, biodegradable materials mainly include natural polymer materials such as cellulose, polypeptides, chitin, collagen, and synthetic polymer materials such as polyamino acids, polyesters, and polylactic acid. Natural polymer materials have better environmental compatibility than synthetic polymer materials and are a more environmentally friendly type of material, which can make the materials that constitute the materials completely return to the ecological cycle after the end of their service life. For example, the Chinese patent document with publication number CN118580540A discloses a method for preparing a high-temperature and high-humidity easily fully biodegradable plastic film. The biodegradable plastic film prepared according to this method has excellent mechanical properties and degradation ability, but it needs to introduce insect eggs and compost to achieve degradation. The Chinese patent document with publication number CN102181077A discloses a fully biodegradable film, the main formula components of which are starch and polyvinyl alcohol, which can achieve the indicators of 180-day degradation and 12-week disintegration of 90% specified in the EN13432 standard. In the field of biodegradation, composting or hydrothermal reactions under specific conditions are widely used to achieve material degradation, which greatly increases the cost of material use and recycling.

[0004] Simplifying the degradation conditions of materials to be able to be completed in the natural environment and achieving natural degradation in the true sense is one of the current research and development hotspots of degradable materials. For example, the Chinese patent document with publication number CN118048023A discloses a polymer material that can be degraded in the natural environment, a preparation method and an application. The material uses raw materials such as bio-based polymer materials, cellulase, amylase, diphosphate pyridine nucleotides, triphosphate pyridine nucleotides, and modified starch. Through grafting modification, extrusion granulation and other processes, bacteria and microorganisms in the natural environment are prepared to completely decompose the material. It does not require high-temperature industrial centralized collection and degradation such as industrial composting, but it involves many preparation raw materials and a relatively complicated process. If natural polymer materials are directly used to prepare degradable composite materials in the natural environment, in order to meet the use requirements, it is also necessary to overcome the disadvantage of insufficient toughness of natural polymer materials. And there are still great difficulties in preparing soil degradable materials with both flexibility and toughness by composite preparation of natural polymer materials and mineral-based materials. Therefore, it is of great research and application value to develop an organic-inorganic composite material that can be degraded in a natural soil environment. Summary of the invention

[0005] The present invention provides a degradable organic-inorganic composite film and a preparation method thereof. The organic-inorganic composite film has adjustable mechanical properties and high toughness. The inorganic structural units are uniformly dispersed in an organic matrix in the form of small-sized high aspect ratio crystals, which effectively improves the organic-inorganic phase interface. The film can be naturally and directly degraded in the soil, and has broad application prospects in the fields of packaging, agriculture, and medical treatment.

[0006] The specific technical solutions adopted are as follows:

[0007] A method for preparing a degradable organic-inorganic composite film comprises the following steps:

[0008] (1) preparing a calcium phosphate nanocluster precursor using an organic amine stabilizer, a calcium source, a phosphorus source and an organic solvent, and further separating to obtain calcium phosphate nanocluster;

[0009] (2) Calcium phosphate nanoclusters and natural polymer materials are mixed to obtain a uniformly dispersed emulsion, wherein the natural polymer materials include carboxymethyl chitosan and alginate, and the emulsion is used to form a film. During the film forming process, the calcium phosphate nanoclusters are transformed into crystallized rod-shaped hydroxyapatite nanocrystals and combined with the natural polymer materials to obtain the degradable organic-inorganic composite film.

[0010] The method of the present invention first prepares a calcium phosphate nanocluster colloid, which is used as an inorganic crystal unit precursor; natural polymer materials carboxymethyl chitosan and alginate together form an organic network structure, and the calcium phosphate nanocluster gradually changes into a crystallized rod-shaped hydroxyapatite nanocrystal in the process of forming a composite film from an emulsion, and the calcium ions are ionically bonded to the carboxyl groups in the organic network structure, and the phosphate ions are hydrogen bonded to the hydroxyl groups in the organic network, thereby effectively improving the organic-inorganic interface, and the small-sized rod-shaped crystals with a high aspect ratio provide a large specific surface area, thereby enhancing the bonding strength between the crystal and the organic network. By adjusting the amount of calcium phosphate nanocluster added, a composite film with different mechanical strengths and toughnesses can be obtained.

[0011] Preferably, the organic amine stabilizer is triethylamine, the molar ratio of the organic amine stabilizer, the calcium source and the phosphorus source is 10-20:0.3-1.7:1, and the concentration of the calcium source in the system is 0.01-0.5 mol / L.

[0012] Further preferably, the organic solvent is ethanol, the calcium source is calcium chloride dihydrate, and the phosphorus source is phosphoric acid; the molar ratio of the organic amine stabilizer, the calcium source, and the phosphorus source is 15-20:1-1.2:1, and the concentration of the calcium source in the system is 0.03-0.1 mol / L. Within the above range, it is beneficial to promote the formation of calcium phosphate nanoclusters and avoid unnecessary increase in raw material costs.

[0013] Specifically, an organic amine stabilizer, a calcium source, a phosphorus source and an organic solvent are reacted at 20 to 30° C. for 10 to 15 hours to prepare a calcium phosphate nanocluster precursor, and the calcium phosphate nanocluster is separated by centrifugation and washing.

[0014] Preferably, in step (2), the mass ratio of calcium phosphate nanoclusters, carboxymethyl chitosan and alginate is 1:0.3-3.6:0.05-0.8.

[0015] More preferably, the alginate is sodium alginate.

[0016] Preferably, the film-making method adopts a casting method, and during the film-making process, an evaporation-induced self-assembly process occurs.

[0017] The invention also provides a degradable organic-inorganic composite film prepared by the preparation method of the degradable organic-inorganic composite film.

[0018] Furthermore, the degradable organic-inorganic composite film contains 52-76wt% of natural polymer materials and 24-48wt% of hydroxyapatite (calculated by thermogravimetric analysis of the product film); preferably contains 52-62wt% of natural polymer materials and 38-48wt% of hydroxyapatite. At the preferred ratio, the composite film has higher toughness.

[0019] The hydroxyapatite is a nanorod-shaped crystal with a length of preferably 10 to 25 nm and a diameter of preferably 2 to 3 nm.

[0020] The degradable organic-inorganic composite film provided by the invention can be degraded in soil, and the mass loss is more than 85% after being buried in the soil for 30 days.

[0021] The invention also provides the application of the degradable organic-inorganic composite film in the fields of packaging, agriculture or medical treatment.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The preparation method of the degradable organic-inorganic composite film provided by the present invention is simple and the reaction conditions are mild. The prepared organic-inorganic composite film is transparent or translucent and has a tensile strength of 17 to 20 MPa and an elastic modulus of 100 to 800 MPa. It is easily degraded in moist soil and its own structure is disintegrated. Only calcium phosphate minerals and trehalose, chitosan and other organic substances and their metabolites are generated. The residual time in the soil is short and the residual amount is small. The damage and pollution to the soil are slight. The degradation products are also helpful for the growth of plants. The film has broad application prospects in the fields of soluble packaging, agriculture or medical treatment.

[0024] (2) In the present invention, inorganic structural units are introduced to enhance the toughness of the natural polymer material-based film, and the inorganic structural units are uniformly dispersed in the natural polymer material matrix in the form of small-sized, high-aspect-ratio crystals, effectively improving the organic-inorganic phase interface, so that the composite film has mechanical properties that meet the requirements of use without affecting environmental compatibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a comparison of optical photographs of the degradable organic-inorganic composite film prepared in Example 1 before and after being buried in the soil for 30 days. The left picture is before landfilling, and the right picture is after landfilling.

[0026] Figure 2 The scanning electron microscope image and transmission electron microscope image of the degradable organic-inorganic composite film prepared in Example 1 are shown, the left image is a scanning electron microscope image, and the right image is a transmission electron microscope image.

[0027] Figure 3The powder X-ray diffraction patterns of the degradable organic-inorganic composite film prepared in Example 1 are compared with those of carboxymethyl chitosan and hydroxyapatite.

[0028] Figure 4 This is a graph showing the tensile test results of the degradable organic-inorganic composite film prepared in Example 1. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the examples and accompanying drawings. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods of the following examples that do not specify specific conditions are usually performed under normal conditions or under conditions recommended by the manufacturer. The content that is not described in detail in this specification sheet belongs to the prior art known to professionals in the field. The experimental materials used in the following examples, if not otherwise specified, can be purchased by conventional biochemical reagent companies.

[0030] Example 1

[0031] 5.88 g of calcium chloride dihydrate was dissolved in 800 mL of ethanol to obtain an ethanol solution of calcium chloride, and then 110.9 mL of triethylamine was added. After stirring for 30 minutes, an ethanol solution of phosphoric acid (3.52 g of phosphoric acid dispersed in 40 mL of ethanol) was slowly added dropwise, and stirred at 25° C. for 12 hours to obtain a calcium phosphate nanocluster precursor. A white colloidal precipitate was obtained by centrifugation, which was washed with a small amount of deionized water and centrifuged to obtain a calcium phosphate nanocluster colloid.

[0032] Take 0.25g of calcium phosphate nanocluster colloid, disperse it in a mixed solution of 12mL of carboxymethyl chitosan aqueous solution (3wt%) and 12mL of sodium alginate aqueous solution (0.5wt%), stir for 3 hours to obtain an emulsion, eliminate bubbles by ultrasound, transfer to a Φ=10cm culture dish and cast it into a film (ventilated and dried at 25°C). During the film-making process, an evaporation-induced self-assembly process occurs, and the calcium phosphate nanoclusters are transformed into crystallized rod-shaped hydroxyapatite nanocrystals combined with natural polymer materials to obtain a degradable organic-inorganic composite film.

[0033] Thermogravimetric analysis of the product film shows that the organic-inorganic composite film obtained in this embodiment contains 70 wt % of natural polymer material and 30 wt % of hydroxyapatite.

[0034] Comparison of optical photographs of the organic-inorganic composite film before and after burial in soil for 30 days. Figure 1 As shown, it is a transparent film, which turns into mineral particles after being buried in the soil for 30 days. Its mass loss is 88.56%, and it is easy to degrade in the soil.

[0035] The cross-section and slice of the organic-inorganic composite film were observed using scanning electron microscopy and transmission electron microscopy. Figure 2 As shown, it can be seen that the interior is uniform and dense, with rod-shaped crystals distributed in the organic matrix, with a length of 10 to 25 nm and a diameter of 2 to 3 nm.

[0036] The comparison of the powder X-ray diffraction patterns of the degradable organic-inorganic composite film, carboxymethyl chitosan and hydroxyapatite is shown in the figure below. Figure 3 As shown, the presence of hydroxyapatite in the film is confirmed.

[0037] The organic-inorganic composite film was subjected to a tensile test, and the results are as follows Figure 4 As shown, the strain at break is 52.18%, the tensile strength is 16.67 MPa, and the elastic modulus is 447 MPa. The mechanical properties meet the requirements of ordinary soluble packaging.

[0038] Example 2

[0039] 0.75 g of the calcium phosphate nanocluster colloid obtained in Example 1 was dispersed in a mixed solution of 12 mL of a carboxymethyl chitosan aqueous solution (3 wt %) and 12 mL of a sodium alginate aqueous solution (0.5 wt %), and stirred for 3 hours to obtain an emulsion. The bubbles were eliminated by ultrasound and the emulsion was transferred to a Φ=10 cm culture dish for film casting (ventilation drying at 25° C.). During the film-making process, an evaporation-induced self-assembly process occurred, and the calcium phosphate nanocluster phase changed into crystallized rod-shaped hydroxyapatite nanocrystals combined with natural polymer materials to obtain a degradable organic-inorganic composite film.

[0040] Thermogravimetric analysis of the product film shows that the organic-inorganic composite film obtained in this embodiment contains 53.5wt% natural polymer material and 47.5wt% hydroxyapatite. The strain of the organic-inorganic composite film at break is 27.81%, the tensile strength is 18.74MPa, and the elastic modulus is 721MPa. It is also easily degraded in the soil, and the mass loss is 86.13% after 30 days of landfill in the soil.

[0041] Example 3

[0042] 0.10 g of the calcium phosphate nanocluster colloid obtained in Example 1 was dispersed in a mixed solution of 12 mL of a carboxymethyl chitosan aqueous solution (3 wt %) and 12 mL of a sodium alginate aqueous solution (0.5 wt %), and stirred for 3 hours to obtain an emulsion. The bubbles were eliminated by ultrasound and the emulsion was transferred to a Φ=10 cm culture dish for film casting (ventilation drying at 25° C.). During the film-making process, an evaporation-induced self-assembly process occurred, and the calcium phosphate nanocluster phase changed into crystallized rod-shaped hydroxyapatite nanocrystals combined with natural polymer materials to obtain a degradable organic-inorganic composite film.

[0043] Thermogravimetric analysis of the product film shows that the organic-inorganic composite film obtained in this embodiment contains 75.7wt% natural polymer material and 24.3wt% hydroxyapatite. The strain of the organic-inorganic composite film at break is 81.57%, the tensile strength is 14.61MPa, and the elastic modulus is 103MPa. It is also easily degraded in the soil, and the mass loss after 30 days of landfill in the soil is 90.46%.

[0044] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a degradable organic-inorganic composite film, characterized in that: The following steps are involved: (1) preparing a calcium phosphate nanocluster precursor using an organic amine stabilizer, a calcium source, a phosphorus source and an organic solvent, and further separating to obtain calcium phosphate nanocluster; (2) Calcium phosphate nanoclusters and natural polymer materials are mixed to obtain a uniformly dispersed emulsion, wherein the natural polymer materials include carboxymethyl chitosan and alginate, and the emulsion is used to form a film. During the film forming process, the calcium phosphate nanoclusters are transformed into crystallized rod-shaped hydroxyapatite nanocrystals and combined with the natural polymer materials to obtain the degradable organic-inorganic composite film.

2. The method for preparing a degradable organic-inorganic composite film according to claim 1, characterized in that: The organic amine stabilizer is triethylamine, the molar ratio of the organic amine stabilizer, the calcium source and the phosphorus source is 10-20:0.3-1.7:1, and the concentration of the calcium source in the system is 0.01-0.5 mol / L.

3. The method for preparing a degradable organic-inorganic composite film according to claim 1, characterized in that: The organic solvent is ethanol, the calcium source is calcium chloride dihydrate, and the phosphorus source is phosphoric acid; the molar ratio of the organic amine stabilizer, the calcium source and the phosphorus source is 15-20:1-1.2:1, and the concentration of the calcium source in the system is 0.03-0.1 mol / L.

4. The method for preparing a degradable organic-inorganic composite film according to claim 1, characterized in that: The calcium phosphate nanocluster precursor is prepared by reacting an organic amine stabilizer, a calcium source, a phosphorus source and an organic solvent at 20-30° C. for 10-15 hours, and the calcium phosphate nanocluster is separated by centrifugation and washing.

5. The method for preparing a degradable organic-inorganic composite film according to claim 1, characterized in that: In step (2), the mass ratio of calcium phosphate nanoclusters, carboxymethyl chitosan and alginate is 1:0.3-3.6:0.05-0.

8.

6. The method for preparing a degradable organic-inorganic composite film according to claim 1, characterized in that: The alginate is sodium alginate.

7. The method for preparing a degradable organic-inorganic composite film according to claim 1, characterized in that: The film-making method adopts the casting method, and during the film-making process, an evaporation-induced self-assembly process occurs.

8. A degradable organic-inorganic composite film obtained according to the method for preparing a degradable organic-inorganic composite film according to any one of claims 1 to 7.

9. The degradable organic-inorganic composite film according to claim 8, characterized in that: It contains 52-76 wt% of natural polymer materials and 24-48 wt% of hydroxyapatite; the hydroxyapatite is a nano-rod crystal with a length of 10-25 nm and a diameter of 2-3 nm.

10. Use of the degradable organic-inorganic composite film according to claim 8 or 9 in the fields of packaging, agriculture or medicine.

Citation Information

Patent Citations

  • Fully biodegradable film meeting EN13432 standard and preparation method thereof

    CN102181077A

  • Natural environment degradable polymer material as well as preparation method and application thereof

    CN118048023A

  • Preparation method of high-temperature and high-humidity easily-fully-biodegradable plastic film

    CN118580540A

  • Composite biopaper based on hydroxyapatite overlength nanowires

    CN106730022A

  • High-strength and high-tenacity organic-inorganic complex macroscale fiber and preparation and application thereof

    CN110117830A

Cited By

  • Preparation method and application of organic-inorganic composite hydrogel with high strength, high inorganic ratio and suitable degradability

    CN119857178A

  • Preparation method and application of a high-strength, high inorganic ratio and suitably degradable organic-inorganic composite hydrogel

    CN119857178B